Migration Based on Refugee Deals Across the World: Comparisons with the EU-Turkey Deal - Elbert, Ľudmila (Migration and Central Europe: Challenges and Legal Responses, 2024)
Refugee deals are increasingly prevalent as states attempt to transfer their obligations under the Refugee Convention. The EU-Turkey deal, originally in the form of the Statement, is the most discussed deal within the European states, however, it is not the only deal considering the status of the refugees. This study aims to examine various refugee deals and compare them with the EU-Turkey deal. The comparative elements are based on the Michigan Guidelines on Protection Elsewhere, which defines basic pre-conditions for compliance with state´s obligations under the Refugee Convention within the arrangements with third states. Therefore, this study discusses the legal nature of selected refugee deals, their compliance with the international refugee law and human rights law, and the necessity for safeguards. The analysis reveals that each arrangement is different. Although all refugee deals aim to strengthen the border security of states and prevent human-trafficking, they have different objectives for transferring asylum seekers, different modus operandi, and impacts on human (and refugee) rights of the asylum seekers. A significant finding is that each asylum case should be assessed individually to ensure that the rights of particular person guaranteed by particular states are not infringed.Keywords: human rights, migration, Refugee Convention, refugee deal, safeguards, third state